A Study on the Revision of Different Editions of"The Red Flag"ZHU Mengmeng (Journal of humanities and social sciences exploratio, 2025)
As a classic work of the"Seventeen Years Literature"(1949-1966)in China,"The Red Flag"has attracted two distinctly different types of critical opinions due to its characteristic combination of aesthetics and politics.Liang Bin,the author,revised the work four times between the 1950s and 1970s.This study takes the four different editions of Liang Bin's red-themed novel"The Red Flag"as the research object,summarizes the differences among the editions,and analyzes the changes across versions by integrating the specific literary creation context,the author's subjective factors,and readers'critical opinions.Based on this,the study selects three dimensions—"modifications to character images","strengthening of class contradictions",and"revision of political discourse"—to explore the political influences behind the textual reconstruction.Revising a classic is an extremely complex process.Liang Bin's revisions to this classic have both enhanced its merits("adding flowers to the brocade")and led to overcorrections.Such issues were unavoidable due to the constraints of the times.Readers should face up to the literary phenomenon of textual revision,explore the literary value contained within it,and rethink the research on the canonization of literary works from the"Seventeen Years Literature"period.
Keywords: Liang Bin; "The Red Flag"; edition revision; political expression